Process innovation capability and innovation performance: mediating effect of product innovation capability (2015)
Although in recent years, investment and the use of resources in R&D by the private sector has increased, the number of innovative companies per se has dropped dramatically in Colombia. However, the studies that have been carried out to analyze this paradox, have only demonstrated the limited positive effects of process innovation capability (IC) on innovation performance (IP). Therefore, the aim of this paper is to determine the mediating effect of product IC on the relationship between process IC and IP, based on a sample of manufacturing firms. Structural equation modeling was used with the method of least squares and a bootstrap-percentile analysis was performed to check the existence of mediation. The results showed that there is a partial mediation. Therefore, the development of IC products is necessary in order to reflect process improvements in the products and to exploit them commercially, thus invigorating the performance